Первые и последние: [рассказы] / Людмила Улицкая - Улицкая Людмила Евгеньевна (Эксмо, 2010)
Экземпляры: Аб (20120323) / Инвентарный номер: 98402 / Цена: 107.00 / Авт.знак: У 48 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6